Morfologia Polínica de Populações Amazônicas de Elaeis oleifera - Martins, Lúcia Helena Pinheiro; Miranda, Ires Paula de Andrade; Nunes, Cley Donizeti (Acta Amazonica, 2003)
Elaeis oleifera (Kunth) Cortés (American oil palm) has advantageous characteristics for hibridization with E. guineensis which vary among populations. In order to contribute to population discrimination, we studied pollen morphology of ten Amazonian populations (Acajatuba, Amatari, Autazes, BR-174, Careiro, Manicoré, Maués, Moura, Novo Aripuanã, Tefé). The acetolysis method was used to eliminate cell contents and enable observations on pollen size, shape, aperture and exine surface. Pollen grains from the Novo Aripuanã population had the largest mean grain size (49 μm) and populations from Amatari, BR-174 and Moura the smallest (42.5 to 44 μm). Pollen is elliptic or piriform, aperture type is monocolpate and exine surface is microreticulate. Pollen grains with morphological abnormalities were also found. Pollen morphology discriminated three groups of Amazonian populations and offers an important tool for population discrimination, especially when associated with other analyses.
Pollen morphology of Amazonian populations of Elaeis oleifera
Keywords: Palynology; Palms; American Oil Palm; Descriptors; Population Discrimination; Palinologia; Palmeiras; Caiaué; Descritores; Discriminação De Populações